Android Based Application For Immersive Image Processing Learning - Sari, Suhaila; Punyavan Usa, Cham Riang; Roslan, Hazli; Mohd Taujuddin, Nik Shahidah Afifi; Mohd, Mohd Norzali; Nazari, Ain (Evolution in Electrical and Electronic Engineering, 2020)
This project aims to develop an Immersive Image Processing learning application to assist in the Image Processing lecture class for Faculty of Electronic and Electrical Engineering (FKEE), in University Tun Hussein Onn Malaysia (UTHM). The immersive Image Processing learning application focuses on seven important modules covered in the Image Processing syllabus. The Graphical User Interface (GUI) development of Android based for Immersive Image Processing learning application is implemented by using Android Studio software. The portability of the Android Image Processing learning application makes users easier to learn image processing and editing image at anywhere and anytime. The application is provided with the notes of the seven modules to users more understanding with the theory. The performance analysis of the Image Processing learning application is evaluated through data collection from survey conducted. Immersive Image Processing learning application market test survey discusses the awareness of respondents on Android Studio software, basic knowledge of respondents in Image Processing course and the implementation of existing Image Processing learning application. In a meanwhile, performance review discusses the performance analysis of the Immersive Image Processing learning application. 100% of the respondents agreed that the application was extremely helpful in assisting in better understanding in image processing.